DIALECTIC RELATIONSHIP OF CONTROL - Vasily V. Chaplya (Advanced Engineering Research)
The analysis of the shadow economy as the result of historical relationships of the control is presented. The role of the relations of the control in promoting the shadow economy is shown. The model of the real historical forms of the economy, which factual matter permits to represent the holistic situation of the content and the mechanism for the implementation of the shadow economy, is offered.